Improving Children’s Fine Motor Skills Through the Mosaic Technique in Group B at Pedang Emas Rambatan Kulon, Indramayu - Shinta Puspita Pertiwi; Irfan Fauzi Rachmat; M. Arif Syarif H (Journal of Educational Sciences, 2026)
Fine motor skill development is an important aspect of early childhood education because it supports children’s readiness for learning activities such as writing, drawing, cutting, and pasting. Initial observations in Group B at TK Pedang Emas Rambatan Kulon, Indramayu, showed that several children still experienced difficulties coordinating hand movements, sticking materials neatly, and maintaining concentration during learning. This study aimed to examine the implementation of the mosaic technique and its contribution to improving children’s fine motor skills. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, comprising planning, action, observation, and reflection stages carried out over two cycles with 17 children aged 5–6 years. Data were collected through observation, documentation, and field notes, then analyzed using qualitative and quantitative approaches. The findings showed a gradual improvement in children’s fine motor development after the mosaic activities were implemented, marked by better hand-eye coordination, finger flexibility, concentration, and task accuracy, along with a more engaging and enjoyable learning atmosphere. The mosaic technique can therefore be considered an effective alternative learning activity for supporting fine motor development in early childhood.